SALES COST EFFICIENCY IN E-COMMERCE BUSINESS FOR ONLINE SELLERS IN SIDOARJO CITY - Nur Aini Anisa; Kurniawati Kurniawati; Syamsul Arifin; Ainun Haqiqi (WORLDVIEW ( Development economic and sharia studies journal ), 2022)
This study aims to describe the analysis of the efficiency of selling costs in the ecommerce business on online sellers in the city of Sidoarjo. The data studied were in the form of interviews conducted by researchers to five sources, namely online sellers in the city of Sidoarjo. Data collection techniques used are interview, observation, and documentation techniques. The data analysis technique used is descriptive qualitative analysis technique. The results of this study are based on analysis of sales cost interview data in the e- commerce business by online sellers that have been carried out efficiently